The evolution of digital relations in the economy and the relevance of financial education in modern society //La evolución de las relaciones digitales en la economía y la relevancia de la educación financiera en la sociedad moderna - Goncharenko, Olga Nikolaevna; Lomonosova, Elena Igorevna; Lomonosov, Dmitrii Aleksandrovich; Mironchuk, Vadim Anatolevich; Progunova, Lada Victorovna (Revista de la Universidad del Zulia, 2020)
Abstract Universities enter educational markets with “digital” services, joining in communities, combining digital and traditional education (online and offline), strengthening ties with business structures, universities and schools. The purpose of the work is to carry out a systematic analysis of the evolution of relationships in education in the context of the digital transformation of society. The formation of socially responsible behaviors of students and Tutors of the educational process is taken into account. These aspects are studied in a systematic way and the financial education procedure is proposed. The main results of the article are the analysis of the system and classification of tasks and digital training processes, development of a procedure (algorithm) for the implementation of the financial training program. Resumen Las universidades ingresan a los mercados educativos con servicios “digitales”, uniéndose en comunidades, combinando educación digital y tradicional (en línea y fuera de línea), fortaleciendo lazos con estructuras empresariales, universidades y escuelas. El propósito del trabajo es realizar un análisis sistemático de la evolución de las relaciones en educación en el contexto de la transformación digital de la sociedad. Se tiene en cuenta la formación de conductas socialmente responsables de los alumnos y Tutores del proceso educativo. Estos aspectos se estudian de manera sistemática y se propone el procedimiento de educación financiera. Los principales resultados del artículo son el análisis del sistema y clasificación de tareas y procesos de formación digital, desarrollo de un procedimiento (algoritmo) para la implementación del programa de formación financiera.